“Chile viene de vuelta". The gremialistas, the conservative-neoliberal synthesis and the crisis of Western Europe (1980-1989) - Santoni, Alessandro; Elgueta, Raúl (Cuadernos de Historia, 2018)
This article focuses in the discursive strategies of right-wing supporters of the Chilean military regime. Its main focus is on the gremialismo, which represents the ultimate expression of the neoliberal-conservative synthesis that characterized the country’s political right-wing parties since the authoritarian years. Drawing on an analysis of articles published on the press related to this group, this article highlights how, within a context of international isolation and in face of the critical attitude of so-called “advanced” capitalist countries of Europe towards the Pinochet regime, a series of representations about the crisis of the West were elaborated. By focusing on the effects of the Welfare State and the decay of traditional moral values, such representations helped overcoming a merely defensive nationalism, thus presenting its national project as an alternative to such crisis.